Sources of Preservice Early Childhood Teachers' Self-Efficacy Beliefs About Teaching Science: A Phenomenological Study - Ahmet Simsar; Shannon G. Davidson (Anı Publishing, 2020)
The purpose of this study is to explore preservice early childhood teacher's self-efficacy beliefs on teaching science and to understand the sources of their self-efficacy beliefs. Three preservice teachers who were enrolled in an early childhood science methods course participated in this study. Through analysis of semi-structured interviews and observational field notes, the results suggest that participants' experiences with curriculum and standards held a negative effect on their self-efficacy beliefs. Additionally, the participants' mentor teachers, prior K-16 science teachers, and the college professor who taught the Science Method Course all had several positive impacts on their self-efficacy beliefs. Participants' science experiences both as K-12 students and in their supervised teaching held both positive and negative effects on their beliefs about teaching science. The results of this study may support teacher educators and researchers in considering carefully the influencing sources of preservice teachers' self-efficacy beliefs for science teaching.